Prognostic value of circulating pigmented cells in African children with malaria. - Kremsner, P; Valim, C; Missinou, M; Olola, C; Krishna, S; Issifou, S; Kombila, M; Bwanaisa, L; Mithwani, S; Newton, C; Agbenyega, T; Pinder, M; et al. (2009)
BACKGROUND: Plasmodium falciparum malaria is a common cause of morbidity in African children, but identifying those who are likely to die is problematic. Previous studies suggested that circulating malarial pigment might be a useful predictor of severity, but none were large enough to detect any association with mortality. METHODS: We used thick blood smears performed on admission for 26,296 children hospitalized with P. falciparum at 1 of 6 hospitals in the Severe Malaria in African Children network to assess the prognostic value of pigment-containing granulocytes, monocytes, and parasites. RESULTS: Although at all but one of the study sites the risk of mortality for subjects presenting with >5 pigmented granulocytes per 200 white blood cells was higher than in subjects with no pigmented granulocytes, adjusted odds ratios estimated through logistic regression, which included other established markers of severe malaria, suggested that associations between pigmented cells and mortality were moderate to nonexistent in most sites. The predictive ability of pigmented cells was low, as measured by the change in the area under the receiver operating characteristic curve of logistic regression models. CONCLUSIONS: Although high levels of pigmented cells were associated with a fatal outcome in some study sites, they were not useful predictors of outcome across Africa.